Effect of Home Bleaching on Microleakage of Fiber-reinforced and Particle-filled Composite Resins - Farahnaz Sharafeddin; Samira Zare; Zahra Javnmardi3 (Tabriz University of Medical Sciences, 2013)
Background and aims. Bleaching may exert some negative effects on existing composite resin restorations. The aim of this study was to evaluate the effect of home bleaching on microleakage of fiber-reinforced and particle-filled composite resins. Materials and methods. Ninety class V cavities (1.5×2×3 mm) were prepared on the buccal surfaces of 90 bovine teeth. The teeth were randomly divided into 6 groups (n=15) and restored as follows: Groups 1 and 2 with Z100, groups 3 and 4 with Z250, and groups 5 and 6 with Nulite F composite resins. All the specimens were thermocycled. Groups 1, 3 and 5 were selected as control groups (without bleaching) and the experimental groups 2, 4 and 6 were bleached with 22% carbamide peroxide gel. All the samples were immersed in 2% basic fuchsin dye for 24 hours and then sectioned longitudinally. Dye penetration was evaluated under a stereomicroscope (×25), at both the gingival and incisal margins. Data were analyzed using Kruskal-Wallis, Mann-Whitney and Wilcoxon tests (α=0.05). Results. Statistical analyses revealed that bleaching gel increased microleakage only at gingival margins with Z250 (P=0.007). Moreover, the control groups showed a statistically significant difference in microleakage at their gingival margins. Nulite F had the maximum microleakage while Z250 showed the minimum (P=0.006). Conclusion. Microleakage of home-bleached restorations might be related to the type of composite resin used.